2016
DOI: 10.5114/aoms.2016.55425
|View full text |Cite
|
Sign up to set email alerts
|

Five years of experience with rituximab plus high-dose dexamethasone for relapsed/refractory chronic lymphocytic leukemia

Abstract: IntroductionHigh-dose methylprednisolone (HDMP) in combination with rituximab is active in the treatment of relapsed/refractory chronic lymphocytic leukemia (CLL), but serious infections are frequent. Recently published data suggested that high-dose dexamethasone might be equally effective as HDMP despite a lower cumulative dose.Material and methodsWe performed retrospective analysis of 60 patients with relapsed/refractory CLL (median age: 66 years; range: 37–86) treated with rituximab plus dexamethasone (R-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
(41 reference statements)
1
7
2
1
Order By: Relevance
“…All considered, the efficacy comparison with other published series is rather difficult; furthermore, whether the addition of cyclophosphamide into the treatment regimen can affect the long‐term outcome for the patients remains controversial. In contrast with previous studies, the presence of del17p deletions and/or TP53 mutations was a significant predictor of shorter progression‐free survival 4,11 …”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…All considered, the efficacy comparison with other published series is rather difficult; furthermore, whether the addition of cyclophosphamide into the treatment regimen can affect the long‐term outcome for the patients remains controversial. In contrast with previous studies, the presence of del17p deletions and/or TP53 mutations was a significant predictor of shorter progression‐free survival 4,11 …”
Section: Discussioncontrasting
confidence: 69%
“…We previously demonstrated that the combination of rituximab with high doses of dexamethasone (R‐Dex) results in a high response rate in relapsed CLL patients. However, the median progression‐free survival is still relatively poor, that is 7‐8 months 4,5 . The present manuscript describes a retrospective analysis assessing whether the addition of cyclophosphamide into the R‐Dex regimen, with the concurrent reduction of the dexamethasone dose, results in a comparable treatment outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Simkovic et al [11] presented retrospective data of Rtx and high-dose dexamethasone combination with an ORR of 75%, median PFS of 8 months, and median OS of 25.5 months. ORR was not dependent on age, but in multivariate analysis, an age of ≥65 years and an absence of therapeutic response (SD/PD) were identified as independent predictors of shorter PFS ( p = 0.002 for both).…”
Section: Discussionmentioning
confidence: 99%
“…Bulky nodes and confluent adenopathy is commonly seen during relapses or, as noted above, in patients at presentation with 17p or 11q deletion (Fig. 2 ) [ 15 , 16 ]. Rare sites of CLL involvement have been reported, including the central nervous system [ 17 , 18 ].…”
Section: Chronic Lymphocytic Leukemia (Cll)/ Small Lymphocytic Lymphomentioning
confidence: 99%